Effect of B₄C variation on the mechanical, fractographic and tribological performance of hybrid composites Al7075/Gr/ZrO₂ (Fracture and Structural Integrity, 2026)
The current study focuses on the influence of varying levels of boron-carbide (B4C) particles on mechanical and tribological characteristics of Al7075 hybrid composites that are strengthened by fixed percentages of graphite (Gr) and zirconia (ZrO2). Hybrid composites were made by stir casting the 2 and 4 wt.% of B4C to Al7075-Gr-ZrO2 matrix in two-steps. The reinforcements were evenly spread throughout the matrix was confirmed by analysis through electron microscopy SEM together with elemental mapping through energy dispersive spectroscopy was utilized. Microstructural properties, tensile, hardness, and wear behaviour of the resulting hybrid composites were tested. The findings suggest that the adding of 4 wt.% B4C shall improve the hardness of Al7075 hybrid reinforced composites to 87 BHN, the UTS by 37% (214 MPa to 293 MPa) and vice versa slight decrease in ductility was attributed due to the addition of B4C. The tribological study revealed that the resistance to wear increased with additions of B4C as the hard ceramic particles served as load bearing phases. These results demonstrate the importance of B4C variation in improving mechanical and tribological behaviour of Al7075-Gr-ZrO2 hybrid reinforced composites in potential structural and aerospace application.
Keywords: Al7075 alloy; hybrid composites; graphite; Zirconia; Boron carbide; Mechanical and wear properties